CREATION OF NEW HETEROGENEOUS CATALYTIC SYSTEMS FOR ACETYLENE AND ACETYLENE AMMONOLYSIS - Soatboev, Komiljon; Daddahodjaev, Abdulla (Educational Research in Universal Sciences, 2023)
Important scientific basis for the selection of catalysts for the hydration of acetylene in the vapor phase. Today, despite the existence of a number of theories on catalyst selection, catalysts for complex parallel and sequential processes are mainly selected empirically. The important scientific basis of the choice of catalysts for the hydration of acetylene in the vapor phase is shown, and the results of the hydration of acetylene in the presence of mono- and bifunctional catalysts in the vapor phase are analyzed.